Renal safety of newer medications. (20th April 2016) - Puttanna, Amar; Varadhan, Lakshminarayanan
Abstract: Over the last 10 years there has been a seismic change in the therapeutic options available to clinicians in managing patients with type 2 diabetes. Three different classes of drugs – the DPP‐4 inhibitors, GLP‐1 receptor agonists and SGLT‐2 inhibitors – as well as new insulins such as degludec have added to the repertoire of the diabetologist. However, one concern still remains and limits the management of the patient with diabetes: renal impairment. Many of the options for managing patients with type 2 diabetes, though generally safe in mild to moderate renal impairment, are restricted or ineffective in severe renal impairment. This article will aim to focus on and discuss the current newer medications, their renal safety and dosing, as well as the implications of use in patients with renal impairment. Copyright © 2016 John Wiley & Sons.